Effect of Averrhoa bilimbi Leaf Extract on Malondialdehyde Levels and Clotting Time of Diabetic Mice - Wardoyo, Regita Ayu Ghizanda; Qomariyah, Nur; Purnama, Erlix Rakhmad (LenteraBio : Berkala Ilmiah Biologi, 2023)
Increased oxidative stress in diabetes mellitus can cause rising malondialdehyde levels and blood coagulation disorders. Leaf extract Averrhoa bilimbi L. has potential as an antioxidant and anticoagulant. This study aimed to determine effect of various doses of Averrhoa bilimbi L. leaf extract on malondialdehyde levels and clotting time in diabetic mice. This study used 24 male mice of the DDY strain induced by alloxan monohydrate 120 mg/kg BB, divided into six treatment groups: non-diabetic group (without alloxan induction), negative control, positive control, extract dose 225 mg/kg BB, 300 mg/kg BB and 375 mg/kg BB with 14 days of treatment. Serum malondialdehyde levels in mice were measured using the TBARS method and the length of clotting time using the capillary tube method. Data analysis using SPSS Shapiro-Wilk test and Lavene test (p>0,05), ANOVA test (p<0,05) followed by Duncan test (p<0,05). The results showed that giving various doses of Averrhoa bilimbi L. leaf extract affects malondialdehyde levels and clotting time in diabetic mice was significant (p<0,05). Extract doses of 300 mg/kg BB and 375 mg/kg BW are more effective in reducing malondialdehyde levels and prolong clotting time in diabetic mice.